Studi Kelimpahan, Hubungan Panjang Berat, Pola Sebaran dan Faktor Kondisi L. intermedia (Gastropoda) - Sendy Lely Merly; Lindon Pane (Cenderawasih University, 2021)
Littorinidae is family of gastropods which found abundantly distributed from roots till the edge of mangroves leafs. The aims of research were to find out the abundance, length-weight relationship, distribution patterns and conditions factors of Littorina intermedia which is associated with mangrove ecosystems in Payum beach. This study conducted in three months start in June until August 2020 in the Mangrove Forest Ecosystem of Payum Merauke Beach. Line transect methods with purposive sampling are using to collected all the samples. There are three stations in this location. The results found in Stasion I tnd., respectively. Both length and weight in the three stations separated into 4 categorize. The higest categories in St. I and St. II belong to category length between 0,96-1,70 cm approximately 638 ind and 84 ind. Reverse with that in St. III belong to category III (1,71-2,45 cm) with 15 ind. Furthermore, for weight analysis dominate with category I with 0,00-0,59 gram which is found in all station. For lenght and weight analysis using Regreation showed Allometric Negative where the growth of length is faster than body weight. Morever the distribution pattern in all sampling site showed in clumped pattern. The condition factor of species L. intermedia, ranges from 0.31 to 26.45 with an average of 1.15. Key Words: Merauke; Weight-Length Relationship; Distribution; Gastropod; Littorina